Franchising Interest: an empirical study of university students’ entrepreneurial intentions - Md. Abu Issa Gazi; Abdullah Al Masud; Mohammad Bin Amin; Sukanta Biswas; Amani Abdalatti; Arafat Jahan Yeana; Abdul Rahman bin S. Senathirajah; Veronika Fenyves (Cogent Education)
The purpose of this study is to investigate the role of core personality-related dispositional traits, namely, desire for autonomy (DFA), need for achievement (NFA), and risk-taking propensity (RTP) in predicting university students’ intentions to pursue franchising as relatively stable motivational antecedents of cognitive and behavioral consequences. A survey of 400 students from various universities in Bangladesh was conducted, employing structural equation modeling (SEM) for data analysis. The findings reveal that while subjective norms and risk-taking propensity do not significantly impact students’ intentions to pursue franchising, NFA and the desire for autonomy emerge as vital factors. The relationship between NFA and entrepreneurial intentions exhibits an inverted U-shaped curve, indicating that moderate levels of achievement motivation enhance attitudes toward franchising and perceived behavioral control (PBC). Furthermore, the study identifies mediating effects wherein attitudes toward franchising and PBC significantly influence the relationship between NFA, RTP, and entrepreneurial intentions. The results yield critical insights for educational institutions and franchisors, emphasizing the importance of aligning support mechanisms with students’ motivational profiles to foster entrepreneurial engagement. By contributing to the understanding of individual motivations and cognitive perceptions affecting franchisee recruitment, this research highlights the need for customized franchising strategies in a competitive landscape. Moreover, it lays the groundwork for future exploration into the dynamics of entrepreneurial intentions within franchising contexts.